Engineered celastrol liposomes with glycyrrhizic acid augment synergistic antitumor efficacy in breast cancer - Zhang, Wei; Li, Jiping; Gao, Xiuli; Liu, Likun; Liang, Hong; Yue, Liling (Frontiers in Oncology, 2025)
Background/ObjectivesBreast cancer treatment remains challenged by the non-specific distribution and systemic toxicity of conventional chemotherapeutics. Celastrol (CEL), a natural compound with antitumor efficacy, faces clinical limitations due to its toxicity and poor solubility. Glycyrrhizic acid (GA), known for tumor-suppressive and membrane-modifying properties, offers potential to enhance targeted drug delivery. This study aimed to develop GA-modified liposomes (GA/LIP-CEL) to synergistically improve CEL’s therapeutic specificity and safety.MethodsGA/LIP-CEL nanoparticles were engineered via thin-film hydration, replacing cholesterol with GA. Physicochemical properties were characterized using TEM, DLS, and HPLC. In vitro evaluations included stability assays, cellular uptake (flow cytometry), cytotoxicity (MTT assay), mitochondrial membrane potential (JC-1 staining), apoptosis (Annexin V/PI), DNA damage (γ-H2AX immunofluorescence), and cell cycle analysis in BT549 breast cancer and MCF-10A normal cells.ResultsGA/LIP-CEL exhibited uniform spherical morphology (122.48 ± 5.37 nm), high drug loading (87.75 ± 2.61%), sustained release (70.13% cumulative release at 24 h), and colloidal stability (negligible size variation over 14 days). Compared to LIP-CEL, GA/LIP-CEL reduced IC50 in BT549 cells while lowering cytotoxicity in MCF-10A cells. Compared with the LIP-CEL group, GA/LIP-CEL treatment demonstrated a statistically significant increase in apoptotic cell proportion (P < 0.05). Enhanced mitochondrial dysfunction (P < 0.05) and DNA (P < 0.05) damage were observed. GA modification improved cellular uptake potentially via regulating membrane fluidity and receptor-mediated endocytosis effects, and induced S-phase arrest (31.66 ± 1.70% cells).ConclusionsGA/LIP-CEL combines GA’s membrane-targeting capabilities with CEL’s therapeutic effects, improving stability, specificity, and safety. This platform represents a novel strategy for precision drug delivery, addressing limitations of conventional systems through natural component integration. Further validation of in vivo performance and pharmacokinetics is warranted to advance clinical translation.